а)2x²-3x-2=0 D=b²-4ac=3²-4*2*(-2)=9+16=25x1=-b+√D/2a=3+5/4=8/4=2x2=-b-√D/2a=3-5/4=-2/4=-0.5Ответ: x1=2, х2=-0,5б)3x²+8x-3=0 D=b²-4ac=64+36= 100x1=-b+√D/2a=-8+10/6=2/6=1/3x2=-b-√D/2a=-8-10/6=-18/6=-3 в)3x²+2x-1=0 D=b²-4ac=4+12=16x1=-b+√D/2a=-2+4/6=2/6=1/3x2=-b-√D/2a=-2-4/6=-6/6=-1 г)2x²+5x-3=0 D=b²-4ac=25+24=49x1=-b+√D/2a=-5+7/4=2/4=1/2=0.5x2=-b-√D/2a=-5-7/4=-12/4=-3д)x²-x-30=0 D=b²-4ac=1+120=121x1=-b+√D/2a=1+11/2=12/2=6x2=-b-√D/2a=1-11/2=-10/2=-5е)x²+x-42=0 D=b²-4ac=1+ 168=169 x1=-1+13/2=12/2=6 x2=-1-13/2=-14/2=-7 ё)2x²+7x-4=0 D=49+32=81x1=-7+9/4=2/4=1/2=0.5 x2=-7-9/4=-16/4=-4ж)5x²-3x-2=0 D=9+40=49 x1=3+7/10=10/10=1 x2=3-7/10=-4/10=-0.4 з)3x²+5x+2=0 D=25-24=1 x1=-5+1/6=-4/6=-2/3 x2=-5-1/6=-6/6=-1 и)2x²-7x+6=0 D=49- 48=1 x1=7+1/4=8/4=2 x2=7-1/4=6/4= 1.5